Music Teachers’ Perspectives and Experiences of Ensemble and Learning Skills - Schiavio, Andrea; Küssner, Mats B.; Williamon, Aaron (Frontiers in Psychology, 2020)
In this article, we report data from two survey studies administered to expert music teachers. Both questionnaires aimed to explore teachers’ pedagogical and performative practice and included open questions elucidating musical skills emerging in groups. The first study focuses on collective teaching settings offered to amateurs, jazz musicians, and university students with various levels of musical expertise. The second reports data from teachers based at the Royal College of Music, London, where the main emphasis is on Western classical repertoire. We integrate both studies and discuss overlapping findings. Despite intrinsic differences concerning the general goals of their teaching and the educational systems in which they operate, our data indicate the ability to “listen and respond to others” as the most important ensemble skill, whereas “time management,” “comparing yourself to the class,” and the “development of responsible ways of learning” emerged as main learning skills. We discuss results and suggestions for future research in teaching and learning music in different contexts in the light of recent theoretical research in the cognitive sciences, considering implications for educators interested in diverse skill levels.